From of Political Behavioral Expression of Citizen According to Democratic Way of Life - Meemana, Pikul; Singmatr, Pol.Sub.Lt. Dr. Sanook (Journal for Developing the Social and Community, 2019)
This research is to study Model and behavioral characteristics, expression of citizen political democracy. The instrument used in the research was this study is a study of document research. The study of concepts, the theory and research related to political behavior in accordance with democracy from libraries and electronic media with a variety of methods, starting with the method of logical thinking, pilot study which is to develop a framework approach from theory foundation. The review of the literature related to finding the right balance of substance and investigate the concept to have more credibility by way of integrating various methods. The study found that Model and behavioral characteristics, expression of citizen political democracy means the actions of individual expression that conveys or about politics in various styles. Including the process of thinking, decision making as well as any action, the willingness of the individual media to politics, participation in political activities, the decision involved in the practice and responsible for projects or activities that are related to politics, such as the political demands, political support, push the public policy and anti-government.